Let 'x' represent the measure of the first angle.
Let 'y' represent the measure of the second angle.
Let 'z' represent the measure of the third angle.
From the statement,
![\begin{gathered} y=4* x=4x \\ y=4x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j7a8h7li5g847rp9djr95suf7ic5u8i9tn.png)
![\begin{gathered} z=18^0+y=18^0+4x \\ z=18^0+4x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1lskkkmi7zem4sjy7u04hrwr9rixhy7b6i.png)
Note: The sum of angles in a triangle is 180°.
Therefore,
![x+4x+18^0+4x=180^0](https://img.qammunity.org/2023/formulas/mathematics/college/vn9btxaqack113jn1i9quca8gr505blle6.png)
Solve for x
![\begin{gathered} x+4x+4x+18^0=180^0 \\ 9x+18^0=180^0 \\ 9x=180^0-18^0 \\ 9x=162^0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pbm6b2wpjo330rnbltgjih3qyl7gv4qbeb.png)
Divide both sides by 6
![\begin{gathered} (9x)/(9)=(162^0)/(9) \\ x=18^0^{} \\ \therefore x=18^0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lv3qjh4d5vczc6bqvxzo9v0750xsarzky1.png)
Substitute x = 27° into the measure of the second angle and solve for y
![\begin{gathered} y=4*18^0=72^0 \\ \therefore y=72^0^{} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/an1d8kp60m47hlw9qy4447ty01ancijmur.png)
Let us now solve for z, which is the third angle
![\begin{gathered} z=18^0+72^0=90^0 \\ \therefore z=90^0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/g2ihj72mwydrxdula0agahwswho1tzk5g3.png)
Hence, the measure of the three angles are
![18^0,72^0,90^0](https://img.qammunity.org/2023/formulas/mathematics/college/h9f18flikz2ievt9dtngdl4bg6xmauw3ar.png)